2016
DOI: 10.7243/2050-120x-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal microneedle-mediated delivery of polymeric lamivudine-loaded nanoparticles

Abstract: Background: The goal of this study was to develop a novel drug delivery system (NDDS) of lamivudine (LAM) to overcome some drawbacks associated with LAM short half-life. To fulfill this goal, polymeric LAM-loaded nanoparticles were prepared and their transdermal deliveries via passive and microneedles (MNs)-mediated transport were investigated. Methods: First, nanoparticles were prepared by double emulsion-solvent evaporation method using polylactic-co-glycolic acid (PLGA) and bovine serum albumin (BSA) as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…They showed that such a prolonged release system could overcome the short half-life of the drug. Furthermore, skin treatment with MNs can result in a two-fold enhancement in the steady-state flux, offering new transport pathways to increase the TDD of the drug-loaded NPs [ 99 ]. In another study, a layer of PLGA NPs containing vitamin D3 was coated on stainless steel MNs [ 100 ].…”
Section: Potential Applications Of Mn Combination With Npsmentioning
confidence: 99%
“…They showed that such a prolonged release system could overcome the short half-life of the drug. Furthermore, skin treatment with MNs can result in a two-fold enhancement in the steady-state flux, offering new transport pathways to increase the TDD of the drug-loaded NPs [ 99 ]. In another study, a layer of PLGA NPs containing vitamin D3 was coated on stainless steel MNs [ 100 ].…”
Section: Potential Applications Of Mn Combination With Npsmentioning
confidence: 99%
“…Ramadan et al (2016) recorded a steady-state NP20 stream values of 7.49 ± 1.46 μg·cm −2 ·hr −1 and 15.77 ± 1.5 μg·cm −2 ·hr −1 for pretreatment skin and the microneedle-related skin. They stated that the steady-state flow of LAM-loaded NP20 across the skin treated with microneedles was substantially higher than that of passive transport across untreated skin [ 112 ]. Patches of microneedles are becoming increasingly relevant as an alternate method for vaccine delivery.…”
Section: Applications Of Microneedles Technologies: Biomedical Applicationsmentioning
confidence: 99%
“…The high drug entrapment rate resulted in an improved physical stability of the drug together with an efficient delivery after skin permeation. This last property was enhanced after microneedles skin pre-treatment [76]. Mannosylated-PLGA NPs were prepared to ensure an efficient delivery of 3TC into brain macrophages.…”
Section: Nucleoside Reverse Transcriptase Inhibitors Nanosystemsmentioning
confidence: 99%